Sintesis Nanohidroksiapatit Berbahan Cangkang Keong Sawah (Pila ampullacea) dengan Variasi Konsentrasi H3PO4 Menggunakan Metode Ultrasound Assisted Precipitation - Karisma, Achmad Dwitama; Kriswanto, Oktavianus Nugroho; Rachmaningtrias, Renda (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Nanohydroxyapatite with the molecular formula Ca10(PO4)6(OH)2 is a calcium phosphate compound that is most widely used in biomedical applications such as bone and dental implants due to its high biocompatibility. The synthesis of nanohydroxyapatite can be carried out using CaCO3 rich materials such rice field snail shell (Pila ampullacea) with a composition of 93.4% CaCO3. The nanohydroxyapatite synthesis method used is Ultrasound Assisted Precipitation. Calcium obtained from the natural material of rice field snail shell (Pila ampullacea) was reacted with H3PO4 precursor at variable 0.3; 0.5; 0.8; 1; 1.3 M until a precipitate of nanohydroxyapatite particles was formed. To determine the effect of H3PO4 concentration, analysis was conducted on the characteristics of the synthesized nanohydroxyapatite. The SEM-EDX analysis revealed a Ca/P ratio of 1.59-1.72 with spherical particle morphology. The FTIR analysis indicated the presence of hydroxyapatite in the sample through the P-O and O-H functional groups.